Macromolecular factor VIII complex: functional and structural heterogeneity observed in von Willebrand swine with transfusion. - Griggs, T R (1977)
The physiologic activities concerned with hemostasis and associated with the Factor VIII macromolecular complex were investigated in swine with von Willebrand's disease after infusion of cryoprecipitate, a lyophilized Factor VIII concentrate, or porcine serum. Immediately after each infusion the various activities antihemophilic factor, von Willebrand platelet aggregating factor, and Factor VIII-related antigen, were elevated in approximate proportion to dose and the bleeding time was shortened.There was a late secondary rise in antihemophilic factor. During the period after infusion, there was a differential fall-off of the various activities, with the bleeding time effect lost first, followed by the von Willebrand platelet aggregating factor and then by the Factor VIII-related antigen. The plasma from swine with von Willebrand's disease late after infusion contained high levels of antihemophilic factor without other detectable activities of the complex. Antihemophilic factor, free of the other components, obtained from plasma from swine with von Willebrand's disease either before or late after infusion eluted from agarose gel columns both as high and lower molecular weight material, unlike normal antihemophilic factor, which had a high molecular weight. In contrast, on ultracentrifugation the antihemophilic factor in these plasma sedimented slowly, even though chromatographically the plasmas contained both high and low molecular weight factor. All of the Factor VIII complex activities in normal porcine plasma sedimented rapidly. These studies demonstrate the heterogeneity of the Factor VIII complex and the apparent dependence of its chromatographic and sedimentation behavior on the functional activities associated with the complex.